Religion as an insulator of delinquency in schools - Wallace, Lisa Hutchinson (American journal of criminal justice, 2005)
While much of the current social control literature has examined the role of religiosity in delinquency, very little attention has been given to its effect on school delinquency. This study sought to fill that void by examining the effectiveness of social bond theory in restraining students from committing school delinquency in a rural Southern county. Further, given the literature that suggests that delinquency varies along developmental stages, the authors also sought to determine the effect of the revised social bond along 6th, 8th, 10th, and 12th grades. Findings indicate that social control theory was moderately successful in explaining school delinquency, while religion achieved significance in the 6th, 8th, and 12th grades, but not the 10th grade. Suggestions for practitioners and policy makers are also discussed.